Upaya Peningkatan Sistem Pengelolaan Limbah Cair Terhadap Efektivitas Pengolahan Limbah Cair Rumah Sakit Umum Pusat Dokter Kariadi Semarang - Irawati, Estri; Wahyuningsih, Nur Endah; Sulistiyani, Sulistiyani (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2007)
ABSTRACT Background: Generally, hospital wastewater constitutes all matter from activity in hospital, that may contain microorganisme, poisonous and radioactive material. The aim of this research was to analyze the efforts of management system improvement to the effectiveness of wastewater treatment of Kariadi Hospital Semarang. Method: This research was an observational research with a cross sectional approach. Data was taken by three methods: observation in the area, interview, and also from the secondary data from hospital management. The data of wastewater quality was taken as a serial data from February until March 2007 for determining the quality after the program of management system improvement. A serial data of wastewater treatment waere taken from January, March, May, August until December 2006 Result: The result of this research was focused to fulfill and improve the tools for effectiveness of management and infrastructure, involving 20 kinds of jos. In the fact, only 60 % or 12 kinds of jobs can be well carried out. . The result of data analysis proved that the efforts of management system of wastewater improvement could be run effectively. Meanwhile the output of its investigation showed that temperature parameter, PH, TSS, BOD, COD, NH3-N, phosfat and E-coli concentration is still under wastewater standard stated by the government number 10, 2004. Conclusion: SWOT analytical describes that the organization favorable for Installation of tools and sanition maintance in quadran II and for the position of stabilisation/rasionalisation to support the turn around strategy Key words : The waste water treatment system management, Hospital